2014
DOI: 10.1007/s12230-014-9392-x
|View full text |Cite
|
Sign up to set email alerts
|

High Stability of a Mitochondrial Genetic Marker mtCOII in Polish Colorado Potato Beetle Populations

Abstract: Colorado potato beetle (CPB) (Leptinotarsa decemlineata (Say in Journal of the Academy of Natural Sciences of Philadelphia 3: 298-331, 1824)) (Coleoptera: Chrysomelidae) is one of the most serious potato pests. It has been reported worldwide, from North America to Europe and Asia. In this study we analyzed the genetic diversity of a mitochondrial DNA marker -a second subunit of cytochrome oxidase (mtCOII) in Polish CPB populations to assess the possible changes of this gene sequence over time and over the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Our study revealed a high degree of homogeneity of population structure in Europe (and even in Northern Asia), a result consistent with previous studies in Europe (Grapputo et al, 2005; Przybylska et al, 2014; Sidorenko & Berezovska, 2002). Beyond a single founder, low genetic differentiation can be explained by strong gene flow, which was previously thought to be detrimental to local adaptation (Lenormand, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed a high degree of homogeneity of population structure in Europe (and even in Northern Asia), a result consistent with previous studies in Europe (Grapputo et al, 2005; Przybylska et al, 2014; Sidorenko & Berezovska, 2002). Beyond a single founder, low genetic differentiation can be explained by strong gene flow, which was previously thought to be detrimental to local adaptation (Lenormand, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…There are several studies on CPB populations that used molecular markers (Jacobson & Hsiao, 1983;Azeredo-Espin et al, 1991, 1996Zehnder et al, 1992;Sidorenko et al, 2000;Hawthorne, 2001;Sidorenko & Berezovska, 2002;Grapputo et al, 2005;Grapputo, 2006;Lorite et al, 2013;Zhang et al, 2013;Przybylska et al, 2014;Izzo et al, 2018;Yang et al, 2020), including analyses based on sequencing the whole genome (Crossley et al, 2017;Cohen et al, 2021). These methods are promising for the investigation of intra-and interpopulation polymorphism, as well as migration routes and microevolutionary processes accompanying the formation of the current CPB range (Udalov & Benkovskaya, 2011).…”
Section: Preparation Of Karyological Slidesmentioning
confidence: 99%
“…37,38 The microsatellite markers of CPB have been developed 39 and used to study invasive populations of CPB in different parts of the world. 8,22,40 Using different molecular markers [such as isozyme, random amplification of polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP), microsatellite, and mtDNA gene region], the colonization process and genetic differentiation between different populations of the CPB were investigated from local to continental scales 8,22,35,[39][40][41][42][43][44][45][46] for example in North America and Europe. 22,35 Early studies based on isozyme variation showed genetic differentiation between Mexican and American populations, indicating that Mexico is the origin of invasive CPB populations.…”
Section: Introductionmentioning
confidence: 99%